The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1088/1755-1315/315/5/052030
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cultivation technologies of agricultural crops with the use of machines and tools of domestic and foreign production for the dry area of the South of Russia

Abstract: The problems of improving the tillage systems and crop cultivation technologies are of particular relevance both in terms of energy savings and, in general, resource conservation. The article describes various tillage systems using machines and implements of domestic and foreign production for the arid zone of southern Russia. The initial position in the development of cultivation technology of crops are agroecological requirements of the crop and variety to the growing conditions. Sequential overcoming of fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In addition, the elements that make up fertilizers can directly inhibit the development of fungal pathogens (Golosnoy et al, 2019;Właśniewski et al, 2019). To obtain a high yield of winter wheat, it is necessary to strictly control the amount of applied mineral fertilizers (Al-Saidan et al, 2019;Grechishkina et al, 2019;Korostylev et al, 2019).…”
Section: Problem Statementmentioning
confidence: 99%
“…In addition, the elements that make up fertilizers can directly inhibit the development of fungal pathogens (Golosnoy et al, 2019;Właśniewski et al, 2019). To obtain a high yield of winter wheat, it is necessary to strictly control the amount of applied mineral fertilizers (Al-Saidan et al, 2019;Grechishkina et al, 2019;Korostylev et al, 2019).…”
Section: Problem Statementmentioning
confidence: 99%
“…seed swelling and germination. High salt concentrations in the field cause the death of a large percentage of seedlings, which leads to their thinning [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…However, the salinity impact consists of the osmotic pressure of the soil solution and its physiological imbalance. The impact of these factors during heterotrophic nutrition leads to a decrease in the mobilization of reserve substances for seed germination [8].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of existing designs of combined tillage machines showed that there are some problems in ensuring efficient soil treatment. In particular, poor quality of soil AgroSMART 2019 pulverization by autorotative rollers; absence of the upper rotating rotor, which does not provide quality pulverization of the upper soil layer; soil bulldozing is possible at difficult roller rotation thus increasing the draught resistance [2,3]. In some combined machines, the soil formation coming from a flat tool is broken between two counterrotating rotary agitators through bending deformation and compression strain, which increases the energy consumption.…”
Section: Introductionmentioning
confidence: 99%